Permainan Kartu Sehat sebagai Edukasi Untuk Pencegahan Stunting Fase 10-14 Tahun Program 8000 HPK - Sofiyetti, Sofiyetti; Mustofa, Kartika (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
8000 HPK is a continuation of the 1000 HPK concept which requires full attention to children and adolescents to prevent stunting. Games are one method of nutrition education that is effective in increasing children's knowledge about the importance of balanced nutrition. This research aims to determine the increase in nutritional knowledge using the Healthy Card Game method at SDIT An Nahl, Jambi City as one of the interventions for nutritional problems in school age children in the 10-14 year phase in accordance with the 8000 HPK program to prevent stunting in children, pre-teens and teenagers. The method in this research is Quasi Experimental by comparing the results before and after intervention through pre and post tests. Students are given nutrition education through healthy card games. The respondents in this research were all students at SDIT An Nahl, Jambi City, who were taken as a probability sample. The data obtained will be analyzed statistically using the Wilcoxonn test. The mean value is different between students' knowledge between the pretest and posttest. The research results showed that the average knowledge score before and after the intervention had increased by 1.19 points. With a mean before intervention of 8.03 points and after intervention of 9.22 points. Test analysis using T-Test on Pretest and Posttest respondents. The results of data testing showed a p value = 0.000 <0.05. The research conclusion was that there was a significant difference in knowledge between knowledge before and after the balanced nutrition educational intervention with healthy card games.